2014
DOI: 10.1111/jsm.12327
|View full text |Cite
|
Sign up to set email alerts
|

Low Prolactin Is Associated with Sexual Dysfunction and Psychological or Metabolic Disturbances in Middle-Aged and Elderly Men: The European Male Aging Study (EMAS)

Abstract: Introduction We previously reported that in male patients consulting for sexual dysfunction, low prolactin (PRL) levels were associated with metabolic syndrome (MetS), arteriogenic erectile dysfunction, and incident major cardiovascular events. Aim The aim of this study is to assess the clinical associations of PRL levels in the European Male Ageing Study (EMAS). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 68 publications
(101 reference statements)
5
43
3
4
Order By: Relevance
“…From an etiologic viewpoint, this lack of association appeared to contradict the involvement of testosterone-mediated mechanisms in the pathogenesis of EM 42 . The association of EM with lower levels of prolactin is in line with previous findings, which showed an association between decreased prolactin levels and anxious 43 or depressive 44 symptomatology, most probably because it reflects a lower central serotoninergic tone 45 . Animal models also have shown that prolactin levels in the brain contribute to the modulation of neuronal circuits involved in the regulation of stress responses 46, 47, 48.…”
Section: Discussionsupporting
confidence: 89%
“…From an etiologic viewpoint, this lack of association appeared to contradict the involvement of testosterone-mediated mechanisms in the pathogenesis of EM 42 . The association of EM with lower levels of prolactin is in line with previous findings, which showed an association between decreased prolactin levels and anxious 43 or depressive 44 symptomatology, most probably because it reflects a lower central serotoninergic tone 45 . Animal models also have shown that prolactin levels in the brain contribute to the modulation of neuronal circuits involved in the regulation of stress responses 46, 47, 48.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, bromocriptine, a dopamine agonist that is well known to suppress serum PRL levels, has been shown to effectively improve insulin sensitivity, and has been approved for the treatment for type 2 diabetes mellitus in the United Sates [19]. In contrast, other studies have shown an inverse association between serum PRL levels and metabolic parameters such as cardiovascular events [20], cardiac remodeling [21], diabetes [22,23], metabolic syndrome [22,24], homeostasis model assessment (HOMA) for insulin resistance [25], and adverse lipid profiles [26]. Therefore, the association between serum PRL levels and metabolism in subjects with serum PRL levels within the physiological range requires further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies have been conducted in either individual gender alone [1518, 20, 2426]. Some studies with subjects stratified based on gender did show gender-specific association between serum PRL levels and glucose-induced insulin release [27], cardiac remodeling [21], and metabolic syndrome [22].…”
Section: Introductionmentioning
confidence: 99%
“…A contrasting finding was recently reported by a European observational cohort study of 2948 communitydwelling men [41].…”
Section: Discussionmentioning
confidence: 83%